Hearing parents' voices: A priority-setting workshop to inform a suite of psychological resources for parents of children with rare genetic epilepsies - Suzanne M. Nevin; Claire E. Wakefield; Ann Dadich; Fleur LeMarne; Rebecca Macintosh; Erin Beavis; Rani Sachdev; Ann Bye; Kenneth Nunn; Elizabeth E. Palmer (Elsevier, 2022)
Objective: To understand parents' of children with developmental and epileptic encephalopathies needs and preferences for psychological resources. Methods: Using a person-based approach, a multidisciplinary panel of clinician and researchers (n = 9) hosted a priority-setting workshop to 1) understand parents' needs and preferences for psychological resources and 2) to develop 'guiding principles' to inform a future suite of psychological resources. The multidisciplinary panel analysed the parent priority-setting workshop data, using a combination of thematic and lexical analysis. Results: Thematic analysis identified six key domains wherein parents (n = 8) prioritised a need for psychological resources to support adaptation to their child's genetic DEE diagnosis. Lexical analysis revealed that connection to diagnosis-specific resources provided a pathway to promote enhanced psychological adaptation, by reducing social isolation and reorienting parents towards feelings of hope. Combination of both analyses generated six thematic informed 'guiding principles'. Conclusion: Codesigned psychological resources may help parents to cope with the unique and complex interplay of stressors associated with their child's DEE diagnosis and treatment. Our 'guiding principles' will be translated to inform a future suite of tailored psychological resources. Innovation: This study demonstrates an innovative codesign approach to inform tailored psychological resources for families of children with rare genetic conditions.